Assessing the Impact of 3% Hypertonic Saline Hyperosmolar Therapy on Intubated Children With Isolated Traumatic Brain Injury by Cerebral Oximetry in a Pediatric Emergency Setting. Issue 12 (27th December 2021) - Washer, Leigh-Ann; Abramo, Thomas; Hardgrave, Hailey; Harris, Zena Leah; Meredith, Mark; Moore, Katherine; Dalabih, Abudulah; Williams, David; Jorgenson-Stough, Amy; Crawley, Lee
Abstract : Supplemental digital content is available in the text. Abstract : Background: Intubated pediatric patients with isolated traumatic brain injury (TBI) are a diagnostic challenge for early detection of altered cerebral physiology instigated by trauma-induced increased intracranial pressure (ICP) while preventing secondary neuronal damage (secondary insult detection) and assessing the effects of increased ICP therapeutic interventions (3% hypertonic saline [HTS]). Invasive brain tissue oxygen monitoring is guiding new intensive care unit TBI management but is not pediatric emergency department (PED) readily accessible. Objective measurements on pediatric isolated TBI-altered bihemispheric cerebral physiology and treatment effects of 3% HTS are currently lacking. Cerebral oximetry can assess increased ICP-induced abnormal bihemispheric cerebral physiology by measuring regional tissue oxygenation (rc SO2 ) and cerebral blood volume index (CBVI) and the mechanical cerebrospinal fluid removal effects on the increased ICP-induced abnormal bihemispheric cerebral physiology. In the PED intubated patients with isolated TBI, assessing the 3% HTS therapeutic response is solely by vital signs and limited clinical assessment skills. Objective measurements of the 3% HTS hyperosmolar effects on the PED isolated TBI patients' altered bihemispheric cerebral physiology are lacking. We believe that bihemispheric rc SO2 and CBVI could elucidate similar data on 3% HTS impact and influence in the intubated isolated TBI patients. Objective: This study aimed to analyze the effects of 3% HTS on bihemispheric rc SO2 and CBVI in intubated patients with isolated TBI. Methods: An observational, retrospective analysis of bihemispheric rc SO2 and CBVI readings in intubated pediatric patients with isolated TBI receiving 3% HTS infusions, was performed. Results: From 2010 to 2017, 207 intubated patients with isolated TBI received 3% HTS infusions (median age, 2.9 [1.1–6.9 years]; preintubation Glasgow Coma Scale score, 7 [6–8]). The results were as follows: initial pre−3% HTS, 43% (39.5% to 47.5%; left) and 38% (35% to 42%; right) for rc SO2 < 60%, and 8 (−28 to 21; left) and −15 (−34 to 22; right) for CBVI; post–3% HTS, 68.5% (59.3% to 76%, P < 0.0001; left) and 62.5% (56.0% to 74.8%, P < 0.0001; right) for rc SO2 < 60%, and 12 (−7 to 24, P = 0.04; left) and 14 (−21 to 22, P < 0.0001; right) for CBVI; initial pre–3% HTS, 90% (83% to 91%; left) and 87% (82% to 92%; right) for rc SO2 > 80%, and 16.5 (6 to 33, P < 0.0001; left) and 16.8 (−2.5 to 27.5, P = 0.005; right) for CBVI; and post–3% HTS, 69% (62% to 72.5%, P < 0.0001; left) and 63% (59% to 72%, P < 0.0001; right) for rc SO2 > 80%, and 16.5 (6 to 33, P < 0.0001; left) and 16.8 (−2.5 to 27.5, P = 0.005; right) for CBVI. The following results for cerebral pathology pre–3% HTS were as follows: epidural: 85% (58% to 88.5%) for left rc SO2 and −9.25 (−34 to 19) for left CBVI, and 85.5% (57.5% to 89%) for right rc SO2 and −12.5 (−21 to 27) for CBVI; subdural: 45% (38% to 54%) for left rc SO2 and −9.5 (−25 to 19) for left CBVI, and 40% (33% to 49%) for right rc SO2 and −15 (−30.5 to 5) for CBVI. The following results for cerebral pathology post–3% HTS were as follows: epidural: 66% (58% to 69%, P = 0.03) for left rc SO2 and 15 (−1 to 21, P = 0.0004) for left CBVI, and 63% (52% to 72%, P = 0.009) for right rc SO2, and 15.5 (−22 to 24, P = 0.02) for CBVI; subdural: 63% (56% to 72%, P < 0.0001) for left rc SO2 and 9 (−20 to 22, P < 0.0001) for left CBVI, and 62.5% (48% to 73%, P < 0.0001) for right rc SO2, and 3 (−26 to 22, P < 0.0001) for CBVI. Overall, heart rate showed no significant change. Three percent HTS effect on interhemispheric rc SO2 difference >10 showed rc SO2 < 60%, and subdural hematomas had the greatest reduction ( P < 0.001). The greatest positive changes occurred in bihemispheric or one-hemispheric rc SO2 < 60% with an interhemispheric discordance rc SO2 > 10 and required the greatest number of 3% HTS infusions. For 3% HTS 15% rc SO2 change time effect, all patients achieved positive change with subdural hematomas and hemispheric rc SO2 readings <60% with the shortest achievement time of 1.2 minutes (0.59–1.75; P < 0.001). Conclusions: In intubated pediatric patients with isolated TBI who received 3% HTS infusions, bihemispheric rc SO2 and CBVI readings immediately detected and trended the 3% HTS effects on the trauma-induced cerebral pathophysiology. The 3% HTS infusion produced a significant improvement in rc SO2 and CBVI readings and a reduction in interhemispheric rc SO2 discordance differences. In patients with bihemispheric or one-hemispheric rc SO2 readings <60% with or without an interhemispheric discordance, rc SO2 > 10 demonstrated the greatest significant positive delta change and required the greatest numbers of 3% HTS infusions. Overall, 3% HTS produced a significant positive 15% change within 2.1 minutes of infusion, whereas heart rate showed no significant change. During trauma neuroresuscitation, especially in intubated isolated TBI patients requiring 3% HTS, cerebral oximetry has shown its functionality as a rapid adjunct neurological, therapeutic assessment tool and should be considered in the initial emergency department pediatric trauma neurological assessment and neuroresuscitation regimen.